Impact of IgA isoforms on their ability to activate dendritic cells and to prime T cells. Issue 9 (28th April 2020) - Gayet, Rémi; Michaud, Eva; Nicoli, Francesco; Chanut, Blandine; Paul, Mireille; Rochereau, Nicolas; Guillon, Christophe; He, Zhiguo; Papagno, Laura; Bioley, Gilles; Corthesy, Blaise; Paul, Stéphane
Abstract: Human IgA could be from different isotypes (IgA1/IgA2) and/or isoforms (monomeric, dimeric, or secretory). Monomeric IgA mainly IgA1 are considered as an anti‐inflammatory isotype whereas dimeric/secretory IgA have clearly dual pro‐ and anti‐inflammatory effects. Here, we show that IgA isotypes and isoforms display different binding abilities to FcαRI, Dectin‐1, DC‐SIGN, and CD71 on monocyte‐derived dendritic cells (moDC). We describe that IgA regulate the expression of their own receptors and trigger modulation of moDC maturation. We also demonstrate that dimeric IgA2 and IgA1 induce different inflammatory responses leading to cytotoxic CD8 + T cells activation. moDC stimulation by dimeric IgA2 was followed by a strong pro‐inflammatory effect. Our study highlights differences regarding IgA isotypes and isoforms in the context of DC conditioning. Further investigations are needed on the activation of adaptive immunity by IgA in the context of microbiota/IgA complexes during antibody‐mediated immune selection. Abstract : IgA isotypes and isoforms bind on different receptors on moDC and regulate their maturation. Monomeric IgA have low capacity to promote DC activation. Dimeric IgA2 promote inflammatory responses leading to cytotoxic CD8 + T cells activation.